Korelasi Antara Pola Makan, Cara Menggosok Gigi, Pengetahuan dan Sikap dengan Status Karies Gigi Pada Siswa Sekolah Menengah Pertama - Riszki Riszki; Sulastrianah Sulastrianah (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2015)
Dental Caries is one of the most common mouth disease in children. According to the data obtained from Public Health Centre in North Buton regency, since 2011 to 2013 there were 304, 141 and 167 cases of dental caries respectively in Kulisusu District, placing the dental caries at the eigth rank. The aim of this study is to determine the correlation between dietary habit, way of teeth brushing, knowledge and attitude in dental health with dental caries status at SMPN 4 Kulisusu in North Buton regency in 2014. The design of this study is analytic observational with cross sectional approach. The population was consist of 98 students and the samples were obtained by total sampling method. A questionnaire was distributed to measure dietary habit, way of teeth brushing, knowledge and attitude. The Dental caries status was obtained using DMF-T Index.The data analyzed by conducting Somer’s test at the significance level 0,05. The result of this study showed that 60,2% respondent have poor dietary habit, 68,4% respondent not brushing their teeth with good manner, 39,8% respondent do not have good knowledge about dental health and 51,0% respondent do not have good attitude in dental care.According to DMF-T index, 10,2% have very high index, 25,5% have high index, 37,8%, have moderate index, 18,4% have low index and 8,1% have very low index. The conclusions of the study showed that there were statistically significant relationships between dietary habit, way of teeth brushing and attitude with dental caries status (p = 0,001,   0,000, and 0,031 respectively). Knowledge has no statistically significant relationship with dental caries status (p-Value = 0,867).Keywords: dental caries status, dietary habit, way of teeth brushing, knowledge, attitude, Junior high School